2014
DOI: 10.1002/cyto.b.21202
|View full text |Cite
|
Sign up to set email alerts
|

The application of flow cytometry for evaluating biological aggressiveness of intracranial meningiomas

Abstract: Background: Meningiomas have classically been considered to include benign and atypical/anaplastic tumors. Despite the availability of clinical and pathologic parameters for prognostic prediction prognosis, the behavior of each meningioma may be difficult to predict. Here, we used DNA flow-cytometric studies to predict biological tumor behaviors of intracranial meningiomas.Methods: The specimens were obtained from fresh tumoral tissues of 43 microsurgically resected meningiomas as approved by the institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…To overcome these current limitations, the present study was initiated to assess the value of iFC in the treatment of meningiomas. There have been some pilot studies regarding the effectiveness of flow cytometry in investigating the biological aggressiveness of meningiomas . With the aid of a newly developed kit solution, iFC has become readily available .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these current limitations, the present study was initiated to assess the value of iFC in the treatment of meningiomas. There have been some pilot studies regarding the effectiveness of flow cytometry in investigating the biological aggressiveness of meningiomas . With the aid of a newly developed kit solution, iFC has become readily available .…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent article by Lin et alon the value of flow cytometry in predicting biological tumor behaviors of intracranial meningiomas (1). Meningiomas are among the most frequent benign intracranial tumors, accounting for 30% of all primary intracranial tumors.…”
Section: Dear Editormentioning
confidence: 99%
“…Ploidy status was not significantly associated with recurrence-free survival [21]. Lin et al, in a study of 43 patients with meningioma, found that the best cutoff value for the discrimination of grade 1 from grade 2 meningiomas was the G 2 /M-phase and S + G 2 /M-phase fractions of 5.12 and 7.52%, respectively [22]. Sampling was always performed from the tumor's core.…”
Section: Discussionmentioning
confidence: 99%